Nigeria’s role in sustaining democracy in Cote d’Ivoire through sub-regional organizations (2010-2014) - Alkali, Bello Muazu (2024)
Over the past three decades, Nigeria has played a pivotal role in promoting regional peace, order, and democratic stability in West Africa through the intervention mechanisms of sub-regional organizations. Although much of the literature covers Nigeria's active involvement in peace-making, peacekeeping, and peace-building missions, the political conflict in Côte d'Ivoire that erupted in 2010, along with the subsequent civil war, has not been extensively explored, especially regarding Nigeria’s intervention thro ugh sub-regional organizations. As a regional power in West Africa, Nigeria's intervention was crucial for ensuring regional stability during the conflict between incumbent President Laurent Gbagbo, who refused to relinquish power, and the declared election winner, Alassane Ouattara. Nigeria's involvement was instrumental in restoring Côte d'Ivoire to democratic stability. This study examines Nigeria's role in resolving the post-election conflict in Côte d'Ivoire from 2010 to 2014 by using an explorative and descriptive qualitative methodology grounded in role and role model theories. By adopting an interpretivist approach, the study relies on a diverse range of data sources, including in-depth interviews, documentary analysis, reports, speeches, archival sources, newspapers, journal articles, theses, and textbooks. Fourteen respondents from various government agencies were interviewed, and the acquired data was thematically analyzed using a deductive approach. The study identifies Nigeria's foreign policy as a key instrument that enables the country to actively promote regional peace and stability. It also reveals that Nigeria's material advantages, such as military capability, economic strength, high GDP, and population, alongside non-material factors like institutional and ideological influence, have cemented its status as a regional hegemon. These advantages allowed Nigeria to play a pivotal role in restoring peace and stability to Côte d'Ivoire during the conflict. Overall, the study contributes to the intellectual debate on state foreign policy and the role of regional powers within regional and sub - regional organizations. It suggests that Nigeria should continue to fulfil its role through a multilateral approach to maintain regional peace, order, and democratic stability.